Parameter optimization of fluted-roller meter using discrete element method - Huang, Yuxiang; Wang, Botao; Yao, Yuxiang; Ding, Shangpeng; Zhang, Junchang; Zhu, Ruixiang (International Journal of Agricultural and Biological Engineering, 2018)
The most important performance indicator of a fertilizer metering mechanism is the evenness of fertilizer flow. In this study, a regression mathematical model between the key operating parameters of the fluted roller meter and the flow evenness was developed to simulate a fluted-roller meter for metering diammonium phosphate fertilizer using the discrete element method (DEM). The model was verified by bench test using the same equipment and parameters as the DEM model. Selected working parameters of the fluted-roller meter, including roll length (L), roll rotational speed (n), and flap angle (α) (for fertilizer discharge control), were optimized to maximize the flow evenness. Flow evenness was assessed by the coefficient of variation (CV) of the discharging mass during the operation. The simulation and experiment results showed the similar trends, in terms of effects of machine parameters on the CV. The relative errors ranged from 0.2% to 34.6% with a mean of 10.5%. This demonstrated that the DEM model was feasible to simulate the metering process of the fluted-roller meter. The machine parameters that significantly affected the values of CV in descending order were α, L and n. Both simulation and measurement results revealed that the optimal machine parameters, represented by the minimum value of CV, were observed at L = 45 mm, n = 55 r/min and α = 22.5°. This combination of parameters returned CV values of 10.89% and 9.55% for simulations and measurements, respectively. The study provided useful information for guiding the design and selection of machine parameters for metering devices for fertilizer applications.Keywords: discrete element method, fertilizer, flow evenness, fluted-roller meter, optimizationDOI: 10.25165/j.ijabe.20181106.3573Citation: Huang Y X, Wang B T, Yao Y X, Ding S P, Zhang J C, Zhu R X. Parameter optimization of fluted-roller meter using discrete element method. Int J Agric & Biol Eng, 2018; 11(6): 65–72.